The epidemiology of khat (catha edulis) chewing and alcohol consumption among pregnant women in Ethiopia: A systematic review and meta-analysis. - Biruk Wogayehu; Tsegaye Demissie; Eskinder Wolka; Mekuriaw Alemayehu; Kassa Daka (Public Library of Science (PLoS), 2023)
The use of khat (Catha edulis) and alcohol during pregnancy is a serious public health problem that has been associated with a number of harmful outcomes for both the fetus and the mother's health. There has been no systematic review with meta-analysis to determine risk factors associated with khat and alcohol use among pregnant women in Ethiopia. Therefore, we aimed to determine the pooled prevalence and risk factors of khat and alcohol use during pregnancy in Ethiopia. This review has been registered in PROSPERO with protocol ID: CRD42023395115. Studies identified from PubMed, Google Scholar, the WHO African Index Medicus, the Cochrane Library, African Journal Online, and Science Direct. Articles published from January 1, 2000 to February 10, 2023 were included. We searched for articles that included any combination of the following key terms: "khat", "qat", "alcohol", "ethanol", "prevalence", "factors", "pregnant" and "Ethiopia". Two reviewers worked independently to screen studies and extract data. A funnel plot and Egger's regression test were used to test publication bias. A forest plot was used to present the pooled prevalence and odds ratio with a 95% confidence interval (CI) using the random effect model. I2 metrics were used to assess heterogeneity. The meta-analysis was carried out with Stata 14.0 software. Nine hundred sixty-two records were retrieved from different sources, and 23 studies were included in the final analysis. The pooled prevalence of khat use and alcohol drinking during pregnancy was 26.6% (95% CI 17.8, 35.5) and 31.65% (95% CI: 21.8, 41.5), respectively. Partner khat use (OR 5.9 [95% CI (2.4, 14.5)]) was associated factor for khat use during pregnancy. Low educational level (OR 2.54 [95% CI (1.8, 3.5)]), pre-pregnancy alcohol use (OR 3.5 [95% CI (2.6, 4.7)]), unplanned pregnancy (OR 2.7 [95% CI (1.8, 4.0)]), history of abortion (OR 2.3 [95% CI (1.4, 3.7)]), poor social support (OR 3.3 [95% CI (2.0, 5.3)]), and mental distress (OR 2.6 [95% CI (2.0, 3.3)]) were associated factors for alcohol drinking during pregnancy. This review indicated that the magnitude of khat and alcohol use during pregnancy in Ethiopia was high. Targeted interventions for groups of pregnant women at high risk of khat and alcohol use are urgently needed. Community-based health education interventions and point-of-sale warnings are essential to reduce the burden. Future studies should consider the influence of community-level factors on khat and alcohol use during pregnancy.